Comparative study on interpreting pile bearing capacity from CPT result / Nydia Mohamad Yatim - Mohamad Yatim, Nydia (2006)
Prediction of pile capacity is performed, however, the statistical analyses and evaluation of the prediction methods is conducted based on the results of several friction piles installed. Piles were tested to twice working loads, and did not fail during pile load tests. Chin Method was used to predict the ultimate load capacity of the piles. An evaluation scheme was executed to evaluate the CPT methods based on their ability to predict the measured ultimate pile capacity. Several criteria are selected to evaluate the ratio of the predicted to measured pile capacities. The final ranks of each method are obtained by averaging the ranks of the method from the selected criteria. Based on this evaluation, between the 8 methods, some methods will show the best performance in predicting the load carrying capacity of piles driven. The worst prediction method is obtained also, which is very conservative (under predicted pile capacities).